Reaction centers in lipids - Dorogi, Márta (Acta Biologica Szegediensis, 2005)
Specific functional role of physiologically important lipids of the photosynthetic membrane (phosphatidylcholine, cardiolipin and phosphatidylglycerol) was investigated on the thermodynamic and kinetic requirements of the charge movements in bacterial reaction centers. The major effect of these lipids is to increase the stabilization of the separated caharges induced by light excitation during the photosynthetic energy conversion. It can be achieved by (1) changing the redox midpoint potential of the QA/QA-and QB/QB-redox couples, which results in the increase of the free energy gap that drives the QA– to QB electron transfer or (2) by changing the quinone binding/unbinding equilibrium. This study provides evidence that from kinetic point of view the P+QA-QB → P+QAQB-charge transfer is mainly driven by the change in the enthalpy in LDAO and PC, whereas the entropy contribution is larger if negatively charged lipids are introduced.